Push back, move forward the National Council of Women's Organizations and coalition advocacy - Woliver, Laura R. 1954- (Temple University Press, 2018)
"Push Back, Move Forward is based on 10 years of work studying the coalition dynamics of the National Council of Women's Organizations in Washington, DC, examining when, how, and why that organization has been successful or failed on specific issues, and gleaning larger lessons about coalition organizations"...